ISRA’ILIYYAT DAN PENGARUHNYA TERHADAP KITAB KULLIYYAT RASA’IL AL-NUR KARANGAN SAID AL-NURSI - Baihaqi, Yusuf (Universitas Islam Negeri Raden Intan Lampung, 2016)
Al-Qur’an has been revealed to all mankinds as aguideline in their life. Al-Qur’an is revealed throughmutawatir method and is guaranted by Allah Almightyfrom any amendments. However there is exist themufassirun who has moulded their interpretationswith Isra’iliyyat. These elements are used wheneverthe mufassirun explains about the story of theprophets. Isra’iliyyat influence in tafseer is clearlyvisible, especially in the classical Qur’aniccommentators with the history-oriented. Isra’iliyyatalso gived visible effect on a contemporary tafseer